2009
DOI: 10.1007/s12088-009-0017-x
|View full text |Cite
|
Sign up to set email alerts
|

General microflora, arbuscular mycorrhizal colonization and occurrence of endophytes in the rhizosphere of two age groups of Ginkgo biloba L.of Indian Central Himalaya

Abstract: The populations of the general microfl ora (bacteria, actinomycetes and fungi) in the rhizosphere and their corresponding non-rhizosphere soil samples of Ginkgo biloba L. of two age groups (Group A, <25 years-young trees; Group B, >60 years-old trees) growing under a temperate location of Indian Himalayan Region (IHR) have been determined. Observations were also made for the diversity, distribution and colonization of arbuscular mycorrhizal (AM) fungi and occurrence of endophytes in roots of G. biloba. The pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Documentation of microbial diversity, including mycorrhizae, in various ecological niches of the Indian Himalayan Region (IHR) with particular reference to biotechnological applications, such as development of microbial inoculants for colder regions, has received attention in recent times [36][37][38][39]. Cold-tolerant bacterial inoculants, possessing plant growth promoting and biocontrol properties, have already been developed in suitable formulations with particular reference to field applications under mountain ecosystems [40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Documentation of microbial diversity, including mycorrhizae, in various ecological niches of the Indian Himalayan Region (IHR) with particular reference to biotechnological applications, such as development of microbial inoculants for colder regions, has received attention in recent times [36][37][38][39]. Cold-tolerant bacterial inoculants, possessing plant growth promoting and biocontrol properties, have already been developed in suitable formulations with particular reference to field applications under mountain ecosystems [40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Research on microbial diversity, with a view of their colonization and applications under temperate locations of Indian Himalayan Region (IHR), has received attention in last two decades . Colonization by endophytic microorganisms and their applications has also got attention . The present study deals with the isolation and characterization of an endophytic fungus from the lateral roots of lentil, a major legume crop grown in IHR.…”
Section: Introductionmentioning
confidence: 99%
“…Kuntse, these authors observed that when the age of seedlings of tropical trees increases the diversity of AMF declines. Similarly, Kumar et al (2009) found higher colonization percentages and densities of AMF spores in young plants compared with old trees of maidenhair (Ginkgo biloba L.). Our results showed the opposite trend, finding more AMF species in the rhizosphere of mature trees than in seedlings, which can be explained by the fact that when trees have been longer periods of time in natural ecosystems, the possibility to be colonized by a more diverse community of AMF propagules can be increased.…”
Section: Discussionmentioning
confidence: 80%